Politik Kewarganegaraan dan Defisit Keterwakilan Perempuan Pengawas Pemilu di Provinsi Riau - Ricky Santoso Muharam; Sudaryatie Sudaryatie (JURNAL HARMONI NUSA BANGSA, 2026)
This article examines women's representation in the membership of the Election Supervisory Agency (Bawaslu) at the district and municipal level in Riau Province for the 2023–2028 term, using the frameworks of citizenship politics and women's political representation. Indonesian Law No. 7 of 2017 mandates that the composition of election management bodies observe a minimum of 30 per cent women's representation, yet the statutory verb "to observe" (memperhatikan) leaves wide interpretive latitude, rendering the norm hortatory rather than binding. The study employs an archival method, treating Bawaslu Decree No. 2571.1/KP.00/K/08/2023 on the appointment of district and municipal Bawaslu members across Riau Province as the primary document, analysed through descriptive quantification and directed content analysis. The findings show that of 54 commissioners across 12 districts and municipalities, only five, or 9 per cent, are women. Seven jurisdictions have no women commissioners at all, and the two that arithmetically exceed the 30 per cent threshold do so only because their membership totals three. These results reveal a pronounced gap between formal and substantive citizenship: women hold equal legal entitlement to serve as election supervisors, yet their effective capacity to exercise that entitlement is constrained by weak normative design, gender-blind recruitment procedures, and a masculinised local political opportunity structure. The article recommends converting the affirmative norm from an advisory formulation into a binding obligation and reforming the governance of election management body selection.